EXAMS: ALITTLEEDUCATION PROBLAMACK NOW LEDEGED - Mesía Maraví, Teodoro Rubén (2014)
The article orieta to review one aspect of the assessment of learning in the university, such as the widely used written examination, in its various forms, as a tool to verify and qualify the level of student learning. Being, as it is, the written exam, perhaps the most widely used to assess students at all levels of the education system tool, it is necessary to conduct a análisi of employment. for this, we consider all (social, educational, psychological, etc.). aspects found in its implementation, highlighting their shortcomings and achievements, to innovate and to redirect their use.